Pengaruh Komunikasi Terhadap Kinerja Pegawai dengan Disiplin Kerja Sebagai Variabel Intervening - Hami Pratama, Jodika; Aprianto, Ronal; Fitria, Fitria; Suwarno, Suwarno (Yayasan Literasi Sains Indonesia, 2022)
The purpose of this study was to determine the effect of Communication on Employee Performance through Work Discipline as an Intervening Variable at the Department of Population Administration and Civil Registration of North Musi Rawas Regency. This research is a quantitative research with the method of collecting data using questionnaires and analyzed using the help of SPSS Statistics 20 with the population and sample in the study amounting to 40 employees. Data analysis activities include data processing and data presentation, performing calculations to describe data and testing hypotheses using statistical tests. The results of the study 1) Communication has an effect on Employee Performance at the Population Administration and Civil Registration Office of North Musi Rawas Regency with a value of tcount = 8.505 > ttable = 1.684 and a significant value obtained is 0.000 <0.05. 2) Communication has an effect on Employee Performance through Work Discipline as an intervening variable at the Department of Population Administration and Civil Registration of North Musi Rawas Regency with a value of tcount = 2,327 > ttable = 1,684. The conclusion that the hypothesis put forward is accepted